2014
DOI: 10.1037/a0037806
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the literature on attentional bias in cocaine use disorder and suggestions for future research.

Abstract: Cocaine use disorder (CUD) continues to be an important public health problem and novel approaches are needed to improve the effectiveness of treatments for CUD. Recently, there has been increased interest in the role of automatic cognition such as attentional bias (AB) in addictive behaviors and AB has been proposed to be a cognitive marker for addictions. Automatic cognition may be particularly relevant to CUD as there is evidence for particularly robust AB to cocaine cues and strong relationships to craving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 106 publications
(251 reference statements)
4
50
0
1
Order By: Relevance
“…Also, it was recently suggested that attentional bias can be assessed more adequately with visual, rather than manual, responses to drug-related stimuli (Dias et al, 2015;Marks et al, 2014b), given that eye fixation time is a sensitive and reliable method for measuring attention allocation to cocaine-related cues with a high test-retest reliability, in contrast to motor response time (Marks et al, 2014a). In summary, it is widely accepted that attentional bias to cocaine-related cues is present in cocainedependent patients (Leeman et al, 2014), but its prognostic value as measured with the addiction Stroop task remains to be more firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was recently suggested that attentional bias can be assessed more adequately with visual, rather than manual, responses to drug-related stimuli (Dias et al, 2015;Marks et al, 2014b), given that eye fixation time is a sensitive and reliable method for measuring attention allocation to cocaine-related cues with a high test-retest reliability, in contrast to motor response time (Marks et al, 2014a). In summary, it is widely accepted that attentional bias to cocaine-related cues is present in cocainedependent patients (Leeman et al, 2014), but its prognostic value as measured with the addiction Stroop task remains to be more firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…Findings such as these have been replicated across various substances of addiction, from cigarettes (e.g., Attwood, O'Sullivan, Leonards, Mackintosh, & Munafò, 2008) to alcohol (e.g., Field, Mogg, Zetteler, & Bradley, 2004), to opiates (e.g., Lubman, Peters, Mogg, Bradley, & Deakin, 2000); however, such attentional capture is not consistently observed in all studies (see, e.g., Bradley, Mogg, Wright, & Field, 2003, Exp. 1) and may depend on the level of substance dependence (Hogarth, Mogg, Bradley, Duka, & Dickinson, 2003), the gender of the participants (Perlato, Santandrea, Libera, & Chelazzi, 2014), and how such bias is measured across various types of addictions (Field & Cox, 2008;Hendrikse et al, 2015;Leeman, Robinson, Waters, & Sofuoglu, 2014).…”
mentioning
confidence: 99%
“…Attention bias modification typically involves re-training individuals to attend to either neutral or positive cues (5). Tasks used for attention bias modification include that of the Stroop task, the Visual probe task and eye-tracking tasks (5,6). To retrain attentional biases, these tasks involve the pairing of probes or words with neutral stimuli instead of the threatening stimuli.…”
Section: Introductionmentioning
confidence: 99%